Brazilian coaches' role in facilitating positive development through university sport (El papel de los entrenadores brasileños para facilitar el desarrollo positivo a través del deporte universitario) - Fernando Santos; Scott Rathwell; Ana Trindade; Rhuan Lima; Vinicius Gobbi; Patricia Gaion (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
In recent years, the role of coaches in fostering Positive Development (PD) has been explored within the context of university sport. However, research in non-English speaking countries such as Brazil, which is highly representative of university sport in Latin America, is still scarce. The purpose of this study was to analyze Brazilian coaches' perceptions of their role in facilitating PD within university sport. In total, 16 university coaches from all regions of Brazil were interviewed (14 male and 2 female). Data were collected through semi-structured interviews. Findings showed that coaches perceived university sport as a conducive platform for fostering both performance and PD outcomes. However, the coaches found it difficult to articulate PD strategies and identified challenges such as lack of time and organizational support. The present study suggests that PD is not well integrated within the current model of university sport in Brazil and highlights a potential need for PD-focused coach education programs.